Structure and wear resistance of electron-beam nitrous coatings; Journal of Friction and Wear; Vol. 33, iss. 5 - Narkevich N. A.; Tagil’tseva D. N.; Durakov V. G.; Shulepov I. A. Ivan Anisimovich; Darenskaya E. A. Elena Anatolievna (2012, 2012)
Title screen